DESAIN SISTEM INFORMASI AKUNTANSI PADA DINAS KEPENDUDUDKAN DAN PENCATATAN SIPIL KOTA PONTIANAK - B41112144, Lianti B41112144 Anti anti (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
LIANTI UNIVERSITAS TANJUNGPURA ABSTRACT This research aims to explore information and describe the accounting information system design in the construction company of four cycles that is revenue cycle and expenditure cycle of Population and Civil Registration Pontianak. The object of research is the Department of Population and Civil Registration Pontianak City.                     The results of this research is the Department of Population and Civil Registration Pontianak City requires accounting functions for recording statements of cash receipts per day in the form of ledger receipts , general ledger cash general ledger cash receipts according to the details of objects , documents as supporting documents in the LPJ acceptance will be handed over to officials of financial aide , and the expenditure cycle transactions , Office of Population and Civil Registration Pontianak City need to separate the functions of treasurer and financial auxiliary official functions . Both of these functions must be separated , the function of treasurer enough to collect and submit the Payment Order ( SPP ) UP / GU / TU / LS along with the completion and functioning of financial aide officials make Payment Order ( SPM ) . Keywords:  Accounting Information Systems, Regional Financial  Accounting, Accounting Information Systems In SKPD.